Ngugi's novels and African history : narrating the nation - Ogude, James (London ; Sterling, Va. : Pluto Press, 1999)
Ngugi wa Thiong'o is one of Africa's most controversial and renowned literary figures. This comprehensive study explores the relationship between history and narrative in his novels.
Abdulla [Petals of Blood] 29 -- 30 -- 31 -- 53-4 -- Achebe, Chinua -- 1 -- 83 -- Agikuyu community -- 16 -- 135 -- identity 41 -- isolation 20 -- land ownership 19-20 -- land ownership 21 -- meaning of names 59 -- myth of origin 7 -- myth of origin 17 -- myth of origin 18 -- myth of origin 21 -- myth of origin 47 -- myth of origin 88-90 -- myth of origin 110 -- mythology 14 -- mythology 23 -- mythology 46 -- mythology 51 -- mythology 88-91 -- mythology 154
Print version record.
Includes bibliographical references (pages 169-175) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Ngũgĩ wa Thiongʼo, -- 1938- -- Knowledge -- History; Ngũgĩ wa Thiongʼo, -- 1938- -- Fictional works; Ngũgĩ wa Thiongʼo, -- 1938-; Historical fiction, Kenyan (English) -- History and criticism; Literature and history -- Africa -- History -- 20th century; Literature and history -- Kenya -- History -- 20th century; Littérature et histoire -- Afrique -- Histoire -- 20e siècle.; Littérature et histoire -- Kenya -- Histoire -- 20e siècle.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; HISTORY -- Africa -- General; History; Criticism and interpretation; Historical fiction, Kenyan (English); Literature and history; Africa; Kenya; Romans; 1900-1999; Criticism, interpretation, etc; History